국내 재래 반왜성“앉은뱅이 밀”의 제과 적성 평가 - 허무룡; 최인덕; 강천식; 김경훈; 박은옥; 박철수; Moo-Ryong Heo; In-Duck Choi; Chin-Sik Kang; Kyung-Hoon Kim; Eun-Ok Park; Chul Soo Park (농업생명과학연구, 2013)
국내 토종 자원으로 알려진 앉은뱅이 밀의 밀가루 특성 밀 과자 적성을 평가하기 위해서 경남 진주시에서 구입한 앉은뱅이 밀의 통밀가루 및 백밀가루와 중형제분기로 제분한 밀가루를 평가하였다. 앉은뱅이 밀 구입처에서 제분된 제분된 통밀가루와 백밀가루는 중형제분기에서 제분된 밀가루에 비하여 밀기울 혼입으로 인하여, 회분과 단백질 함량이 높고 밀가루 색깔이 어두웠고 침전가와 건부율 및 아밀로스 함량은 낮았다. 반죽 시간이나 안정도는 밀가루간에는 차이가 없었지만, 반죽 가수량은 밀기울을 포함한 통밀가루가 높았고, 쿠키 직경이 적게 나타났다. 중형제분기로 제분된 앉은뱅이 밀가루의 밀가루 입도와 손상 전분 함량이 각각 54.44μm와 2.46%로 연질밀 특성을 나타내었으며, 총아라비노자일란 함량과 수용성 아라비노자일란 함량이 각각 28.52%와 9.49% 로 국내 밀 품종보다 높았다. 쿠키 직경은 86.88mm로 수입산 박력분과 유사하였으며, 쿠키 표면의 균열도 쿠키 적성에 적합한 것으로 나타났다. The objective of this study was to evaluate flour properties and cookie quality from Korean landrace, Anzunbaengimil, which cultivated in Gyeongsangnam-do Jinju. Wholemeal and flour of Anzunbaengimil were collected from Jinju and grain also was milled with a Bühler experimental mill. Wholemeal and flour of Anzunbaengimil from Jinju showed higher ash and protein content, darker flour color and lower SDS-sedimentation volume, dry gluten and amylose content than wheat flour milled from experimantal mill due to the bran of wheat gran. Wholemeal and flour of Anzunbaengimil from Jinju showed higher water absorption of mixograph and lower cookie diameter than wheat flour milled from experimental mill, no significant difference was not found in mixing time and mixing tolerance of mixograph. Average particle size of wheat flour and damaged starch content of wheat flour milled from experimental mill were 54.44μm and 2.46%, respectively. These properties of Anzunbaengimil were similar to soft wheat flour. Total and water soluble arabinoxylan of wheat flour milled from experimental mill were 28.52% and 9.49%, respectively, which were higher content than Korean wheat cultivars. Cookie diameter of wheat flour milled from experimental mill was 86.88mm, which comparable to commercial wheat flour for cookie baking. Top grain of wheat flour milled from experimental mill was also comparable to commercial wheat flour for cookie baking